Chat with ChatGPT: Access to cultural heritage with ChatGPT - Yilmazer, Merve; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2023)
Cultural heritage, in the most general sense, refers to the historical accumulations from the past to the present. Digital systems are being integrated as an alternative to physical interventions for the management, maintenance and supervision of cultural heritage sites. For these purposes, advanced intelligent systems such as machine learning and deep learning are generally used. In this study, the competence of ChatGPT, an artificial intelligence robot developed by OpenAI with a high learning rate, in the field of cultural heritage is investigated. Questions such as cultural heritage, digital cultural heritage, protection of cultural heritage, etc. were asked to ChatGPT, and the timeliness and adequacy of the answers produced in response to the questions were evaluated. In addition, a comparison of experimental studies in the literature for the preservation and cultural heritage digitalization sites is also included in this study. © 2023 IEEE.
2023 International Conference on Sustaining Heritage: Innovative and Digital Approaches, ICSH 2023 -- 18 June 2023 through 19 June 2023 -- Virtual, Online -- 198561
Keywords: bard; bing; chatgpt; cultural heritage